2019
DOI: 10.1212/nxg.0000000000000328
|View full text |Cite
|
Sign up to set email alerts
|

Novel pathogenic XK mutations in McLeod syndrome and interaction between XK protein and chorein

Abstract: ObjectiveTo identify XK pathologic mutations in 6 patients with suspected McLeod syndrome (MLS) and a possible interaction between the chorea-acanthocytosis (ChAc)- and MLS-responsible proteins: chorein and XK protein.MethodsErythrocyte membrane proteins from patients with suspected MLS and patients with ChAc, ChAc mutant carriers, and normal controls were analyzed by XK and chorein immunoblotting. We performed mutation analysis and XK immunoblotting to molecularly diagnose the patients with suspected MLS. Lys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 10 publications
2
25
0
Order By: Relevance
“…Because VPS13 family proteins are known to be recruited to different organelles through partner proteins, the phenotypic similarities between ChAc and McLeod Syndrome suggested that XK might be a VPS13A partner protein. This idea is strongly supported by the fact that the two proteins form a complex and colocalize within the cell ( Urata et al , 2019 ; this work). Furthermore, XK is capable of relocalizing VPS13A from lipid droplets to ER subdomains, and two different disease-associated mutations in VPS13A disrupt this relocalization.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Because VPS13 family proteins are known to be recruited to different organelles through partner proteins, the phenotypic similarities between ChAc and McLeod Syndrome suggested that XK might be a VPS13A partner protein. This idea is strongly supported by the fact that the two proteins form a complex and colocalize within the cell ( Urata et al , 2019 ; this work). Furthermore, XK is capable of relocalizing VPS13A from lipid droplets to ER subdomains, and two different disease-associated mutations in VPS13A disrupt this relocalization.…”
Section: Discussionmentioning
confidence: 61%
“…Coimmunoprecipitation was also observed when the situation was reversed, that is, GFP-XK, but not GFP alone, was detected in immunoprecipitates generated using α-VPS13A antibodies ( Figure 1C ). Coimmunoprecipitation of VPS13A and XK was independently discovered by Urata et al (2019) . XK and VPS13A therefore form a complex in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Although the levels of these proteins were all reduced in total signal on the western blots of fractions from Q175 compared to wild-type, their peak distribution was in lower fractions (3–7) and no shift in their percent distribution in the gradient occurred. We also looked at XK, a protein that when mutated produces chorea ( Jung et al, 2003 ; Urata et al, 2019 ) and found no change in levels or distribution occurred in fractionations for XK for Q175/Q7 HD compared to Q7/Q7 striatum.…”
Section: Resultsmentioning
confidence: 99%
“…We also looked at XK, a protein that when mutated produces chorea (Jung et al, 2003;Urata et al, 2019) and found no change in levels or distribution occurred in fractionations for XK for Q175/Q7 HD compared to Q7/Q7 striatum.…”
Section: The Presence Of the Hd Mutation Alters Distribution Of Membrmentioning
confidence: 99%
“…It is therefore of interest that XK is a paralogue of proteins with scrambling activity, although a scrambling function for XK itself remains to be proven [ 61 ]. Notably, cell-based overexpression studies have suggested a physical interaction between XK and VPS13A [ 60 ] and, consistently, reduced levels of VPS13A have been reported in McLeod patients [ 110 ]. However, as the bulk of XK is thought to be primarily localized at the plasma membrane, the functional connection between these two proteins remains to be further explored.…”
Section: Disease Mechanismsmentioning
confidence: 99%